Innovative work behavior in high-tech enterprises: Chain intermediary effect of psychological safety and knowledge sharing - Xu, Ziqing; Suntrayuth, Sid (Frontiers in Psychology, 2022)
This study aims to explore the relationship between organizational innovation climate (OIC) and innovative work behavior (IWB), using psychological safety (PS) and knowledge sharing (KS) as mediating variables. Based on the social cognitive theory (SCT), this study proposes a conceptual framework to explore innovative work behavior. The structural model of the extended SCT model was tested using sample data from 446 R&D staff of high-tech enterprises in China. SPSS 25.0 and AMOS 23.0 were used to test the hypothetical model. The results indicated that organizational innovation climate was positively correlated with psychological safety and innovative work behavior. Psychological safety was positively correlated with innovative work behavior. Knowledge sharing was significantly and positively correlated with innovative work behavior. Moreover, Psychological safety and knowledge sharing play a significant mediating role in the relationship between organizational innovation climate and innovative work behavior, and psychological safety further improves individual innovative work behavior by influencing knowledge sharing among research team members. At the end of the study, this study thoroughly discussed the conclusions, practical implications, limitations, and future research directions of the study.